Research of features of the mercy manifestation of doctors - Shevchenko, Nataliia Fedorivna; Shevchenko, Anatolii Ivanovich (Insight: the psychological dimensions of society, 2020)
The purpose of the article is to highlight resultsof an empirical research of features of the mercy manifestationof doctors.The research methods include theoretical: inductionand deduction, analysis, synthesis, generalization;empirical: “Sacks sentence completiontest” (by J. Sachs, in modification), “Diagnosisof empathic abilities” (by V. Boyko), “Empathicpotential of an individual” (by I. Yusupov), “Diagnosisof social and psychological attitudes of an individualin the motivational sphere” (by O. Potiomkina);mathematical and statistical methods.Results. The research of manifestation of the mercyof the medical staff has shown that most of the studiedparameters are in the range of the average level. Study of the cognitive component manifestation hasshown that respondents can be characterized bya positive perception of help and charity, by a lowerattitude to empathy. Study of the empathic abilities(emotional-and-motivational component) hasshown that the doctors tend to rely on a rationalchannel of empathy, have well-developed guidelinesfor empathy and prefer to create a trusting atmosphere.Research of personal social and psychologicalsets in the motivational and needs sphere(emotional-and-motivational component) hasrecorded an average level of altruistic orientations.Study of manifestation of the behavioral componentof mercy has indicated that the medical staffmainly shows empathy towards parents, towardsthe elderly and towards strangers or unfamiliar people.The average level of empathy in behavior hasbeen stated. Conclusions. The study has confirmedthe assumption that the mercy as an integral personallyand professionally significant quality of a medicalworker is determined by the harmonious developmentof cognitive, emotional-and-motivationaland behavioral components, and it is not manifestedenough in usual conditions of pr ofessional activity.